Preserved learning of implicit regularities with predictive social cues in older adults - Salera, Claudia; Yankouskaya, Ala; Gazzaneo, Maria Daniela; Bonavita, Alessia; Pazzaglia, Mariella; Guariglia, Cecilia; Pecchinenda, Anna (Frontiers in Psychiatry, 2024)
IntroductionWith ageing there are changes in the ability to orient attention, which affect more endogenous than exogenous orienting. However, orienting attention by the gaze direction of others shares characteristics of both exogenous and endogenous attention and it is unclear how it is affected by ageing. Being able to orient attention by the gaze direction of others is important to establish successful social interactions (i.e., joint attention), and when gaze direction predicts where in the environment salient events occur, it helps to successfully navigate the environment.MethodsHere we investigated whether older individuals learn implicit regularities between the direction of eye gaze and a spatial location where salient events occur. We also assessed the association between orienting attention by the gaze of others and loneliness. Seventy older individuals completed the three-items UCLA loneliness scale and the gaze cueing task, in which gaze cues were non-predictive of target location (block 1), but unbeknownst to participants became predictive of the spatial location where the target appeared (block 2) and then, returned to being non-predictive (block 3).ResultsFindings clearly show that older individuals are less able to orient attention by non-predictive gaze cues, but they successfully learn from environmental regularities implemented with direction of eye gaze. This learning biases attention as it enhances the gaze cueing effect even when the regularities are not present. Importantly, gaze cueing was not affected by self-reported loneliness.DiscussionThese findings point to a training strategy to improve joint attention in older individuals.